Feature Engineering for Spike Sorting - Ackerlauer, Arnold (Jihočeská univerzita, 2023)
Spike sorting is the process of identifying the neuron from which a spike originated from and can be used in various applications such as brain-machine interfaces. This thesis is based on simulated, continuous recordings of single neuronal cells. Using several feature engineering techniques we were able to propose a feature set which can be used for spike sorting.
Feature Engineering for Spike Sorting
Keywords: spike sorting; feature engineering; spike sorting; feature engineering